2016
DOI: 10.1542/peds.2016-0218
|View full text |Cite
|
Sign up to set email alerts
|

The Fecal Microbiota Profile and Bronchiolitis in Infants

Abstract: Little is known about the association of gut microbiota, a potentially modifiable factor, with bronchiolitis in infants. We aimed to determine the association of fecal microbiota with bronchiolitis in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 44 publications
(36 reference statements)
10
74
0
Order By: Relevance
“…The present novel finding is intriguing because it is generally considered that a higher bacterial richness and diversity is favorable. Yet, recent studies have demonstrated that a higher bacterial diversity may be associated with diseases . For instance, Huang et al .…”
Section: Discussionmentioning
confidence: 99%
“…The present novel finding is intriguing because it is generally considered that a higher bacterial richness and diversity is favorable. Yet, recent studies have demonstrated that a higher bacterial diversity may be associated with diseases . For instance, Huang et al .…”
Section: Discussionmentioning
confidence: 99%
“…The setting and participants have been reported previously. 18,19 Briefly, using a standardized protocol, we enrolled healthy infants – age-matched within 1.5 months of the cases – from a primary care group practice at Massachusetts General Hospital (Boston, MA) between November 2013 and May 2014. We excluded infants with gestational age <32 weeks, comorbidities, previous lower respiratory infection that resulted in an urgent clinic visit, emergency department visit, or hospitalization, current fever, respiratory illness, or gastrointestinal illness, or antibiotic treatment in the preceding 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…17 To examine the composition of the fecal microbiota, we applied a 16S rRNA gene sequencing approach. Detailed protocol for 16S rRNA gene sequencing has been described previously 18 and was based on methods developed for the National Institutes of Health Human Microbiome Project 19 . In brief, bacterial genomic DNA was extracted using MO BIO PowerMag DNA Isolation Kit (Mo Bio Lab; Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%